Missing at work: Sickness-related absence and subsequent job mobility - Adrian Chadi; Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2015)
Economists often interpret absenteeism as an indicator of effort. Using data from the German Socio-Economic Panel (SOEP) study, this paper offers a comprehensive discussion of this view by analysing various forms of job mobility. The evidence reveals a significantly negative (positive) link between sickness-related absence and the probability of a subsequent promotion (dismissal). In line with the interpretation of absenteeism as a proxy for effort, instrumental variable analyses suggest no causal impact of absence behaviour on the likelihood of such career events when variation in illness-related absence is triggered exogenously. We observe no consistent gender differences in the link between absence and subsequent career events.
Keywords: J16; J22; J63; M51; 330; dismissal; gender difference; German Socio-Economic Panel (SOEP); instrumental variables; job mobility; promotion; sickness-related absence